Distribution of Micro Business Productive Assistance Program (BPUM) for MSMEs Affected by Covid-19 in Nagri Kidul Village - Susmita Maharani; Arief Mulyawan Thoriq; Hana Uswatun Hasanah (Journal of Islamic Economics and Business, 2022)
Seeing the sluggish condition of the MSME economy, several programs were introduced by the government, one of which was the Productive Assistance for Micro Enterprises (BPUM). This policy is contained in the Regulation of the Minister of Cooperatives, Small and Medium Enterprises of the Republic of Indonesia number 6 of 2020 concerning BPUM and BPUM Implementation Guidelines number 98 of 2020. The distribution of the BPUM program is an activity carried out to assist micro business actors affected by COVID-19. This study aims to determine the distribution of the BPUM program in the era of the Covid-19 pandemic in Nagrikidul Village, Purwakarta District, Purwakarta Regency. The type of research used is qualitative with a case study approach that aims to reveal the distribution of the BPUM program. The results of this study indicate that: 1) Distribution of the BPUM Program In the distribution of the BPUM Program to recipients in Nagrikidul Village by all relevant agencies, where the list of recipients is determined by the Central Government. 2) Socio-Economic Impact The government issues a policy of limiting activities such as PSBB to PPKM level, which directly impacts the community's economy. So that it affects daily life, especially household income. Factors that affect the absence of a Standard Operating Procedure (SOP), Inaccurate data, and Limited authority.